Services Technology and Management: Navigating the Digital Frontier - Yadav, Chanchal (Journal of Advanced Research in Service Management, 2023)
In an era marked by rapid technological advancements, Services Technology and Management have emerged as central pillars shaping modern businesses and industries. This abstract provides a concise overview of the comprehensive review, which explores the evolution, current trends, and future prospects of this dynamic domain. The historical journey begins with the early forms of services, tracing their evolution through the Industrial Revolution and the subsequent integration of information technology. Today, services have transcended traditional boundaries, fueling a global economy defined by digital transformation and customer-centricity. Key trends encompass digitalization, automation, customer-centricity, and sustainability, all underpinned by cutting-edge technologies such as cloud computing, AI, blockchain, and IoT. Amid these opportunities, challenges abound, including data privacy, integration complexity, talent gaps, and ethical considerations. Real-world case studies illuminate the impact of services technology and management, from Amazon's cloud computing prowess to Uber's disruptive transportation model. As we look to the future, emerging technologies like 5G, quantum computing, AR/VR, and sustainable practices are poised to redefine the landscape. The abstract underscores the importance of navigating these changes with a commitment to innovation, ethical conduct, and a vision of a world where services enhance human prosperity and well-being. Services Technology and Management beckon us to embrace the digital frontier, where adaptability and wisdom are the compass points guiding us toward a promising horizon.